Potential in bioethanol production from various ethanol fermenting microorganisms using rice husk as substrate - WOOTTICHAI NACHAIWIENG; SAISAMORN LUMYONG; RONACHAI PRATANAPHON; KOICHI YOSHIOKA; CHARTCHAI KHANONGNUCH (Biodiversitas Journal of Biological Diversity, 2015)
Nachaiwieng W, Lumyong S, Pratanapol R, Yoshioka K, Khanongnuch C. 2015. Potential in bioethanol production fromvarious ethanol fermenting microorganisms using rice husk as substrate. Biodiversitas 16: 320-326. Rice husk was investigated as thepotential substrate for bioethanol fermentation. It was collected from five locations in northern Thailand and found that the maincomponent of rice husk approximately 51-54% (w/w) was holocellulose. The sugar composition in rice husk holocellulose was glucose,xylose and arabinose in the ratio 66.68, 27.61 and 5.71%, respectively. Before further fermentation, acid and alkali pretreatment of ricehusk were prior investigated and 2% (w/v) NaOH at 130oC for 30 min was proved to be the most suitable pretreatment method withoutfermenting inhibitors generation. Then, rice husk hydrolysate obtained by enzymatic saccharification with Meicelase enzyme was usedas carbon sources for ethanol fermentation in comparison among 11 ethanol fermenting microorganisms including 3 strains ofSaccharomyces cerevisiae, 3 strains of Zymomonas mobilis, 3 strains of Kluyveromyces marxianus and 2 strains of pentose sugarfermenting microbes, Candida shehatae TISTR 5843 and Pichia stipitis BCC 15191. All three strains of Z. mobilis exhibited the bestethanol fermentation yield, giving the ethanol yield of 0.48 g g-1 available monosaccharides and fermentation profile of each individualgenus was also demonstrated. However, some unutilized sugars still remained in rice husk fermenting medium, therefore, conversion tovaluable products or optimization of co-culture ethanol fermentation needs to be further investigated.